DEVELOPMENT OF HIGH-EFFICIENCY REPLACEMENT FILTERS FOR PURIFICATION OF DRINKING WATER ON HOUSEHOLD FILTER PITCHERS - Bolshak , Anna; Patalashka, Roksolana; Gudim, Nataliia; Liuts, Victoriіa; Shevchuk, Olena (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2023)
Water filter pitchers s are the simplest and most affordable devices for local purification of drinking water from centralized and decentralized water sources. The main filter element of such pitchers is a cartridge containing a mixture of sorption materials that are able to absorb certain impurities from the water. However, as previous studies demonstrated, the quality of water, purified with filter pitcher cartridges currently available on the market, does not usually reach the level sufficient to meet the standards for drinking water, which are specified in the document DSanPin 2.2.4-171 -10 "Hygienic requirements for drinking water intended for human consumption", while maintaining compliance with consumer needs. Therefore, the aim of this study is to develop a cartridge for filter pitchers, which would provide high efficiency of purification of tap water in Kyiv from the most common impurities: chlorine, organic compounds and hardness ions. In this work, 5 newly created cartridge samples with different ratios of sorption material content, drainage material density, cartridge filling density, presence or absence of inert material in the loading were studied to identify the impact of these factors on water purification efficiency and water filtration rate, as well as the connection between these parameters. According to the results of the study, a cartridge for a filter pitcher was proposed and determined its the optimal composition. It provides adjustment of tap water composition, namely: reduction by 60 % of the average concentration of chlorine (per 150 dm3 of water), by 15 % - permanganate oxidizability and by 20 % concentration of hardness ions to standard values at filtration rate not less than 0.15 dm3/min and a resource of 150 dm3. These results were achieved by selecting the optimal ratio of the components of the filter loading mixture and the density of the bottom drainage material.